The Translation Strategies Used in the Finnish Translation of The Free Wee Men - Soosilla, Aigi (My University, 2024)
This paper explores the translation strategies used to translate the dialogue spoken in the children’s fantasy novel The Free Wee Men. The aim and purpose of this research is to analyse and discover the context in which these strategies are commonly used and determine if some strategies are used within a wider scope than others. The material utilised includes two consecutive chapters of The Free Wee Men and its Finnish Translation Vapaat Pikkumiehet, as well as Manuela Perteghella’s categories of translation strategies for dialects and slang. The main method used in the research is comparing and analysing the target text and the source text. The results of the research indicate that there are instances of all five translation strategies used in the Finnish translation of The Free Wee Men. Two strategies, dialect compilation and pseudo-dialect translation, appeared in a particularly wide grammatical and lexical range. While these findings do not prove that aforementioned strategies are “better” in any way for translating dialects, it can be concluded that they might be convenient strategies when it comes to translating those aspects in a dialect.
Keywords: dialect, translation strategies, fiction, context